Early intervention: from conception until to the 6 years (contributes of the filogenesis, sociogenesis and ontogenesis) - Ana Cristina Lavandeira Simões (Universidade Federal de Santa Maria (UFSM), 2008)
The human being is constituted partially by a biological heritage transmited by the genes and a cultural heritage transmited through the interaction with others in the diferent contexts in with he/she's inserted. The individual development(embryogenesis and ontogenesis) is based upon the biological inheritance (filogenesis) and the cultural inheritance (sociogenesis). It is a complex and lifelong process, held by the direct exposure to the environment factors and through the mediatization of the involvement by the more experient beings towards the less experient being in a diversity of contexts conveyed by the society. The study of our species and our historical past are fundamental for the understanding of man and the current society.